The Ancient Medical Sources in the Chapters about Sterility of Rodrigo de Castro’s De universa mulierum medicina - Pinheiro, Cristina (2020)
Rodrigo de Castro (c. 1546–1627) was a Portuguese medical author exiled in Hamburg, where he wrote De universa mulierum medicina (1603). This chapter will identify the ancient sources cited in the chapters about sterility, and analyse how Castro relied upon classical medical, biological, and philosophical texts to structure his views. The chapter considers his suggested types, causes, and therapies for female and male sterility, and the legal, social, and moral implications of sterility. More broadly, the chapter will demonstrate the connections between sexuality, conception, and fertility in early modern medical texts, reconsider the validity of Thomas Laqueur’s influential ‘one-sex model’, and show how early modern authors drew on the authority of ancient medical sources to justify the attribution of blame to men and women in theories of infertility.